Participation of Acoustic and Electric Hearing in Perceiving Musical Sounds - Duret, Sonia; Bigand, Emmanuel; Guigou, Caroline; Marty, Nicolas; Lalitte, Philippe; Bozorg Grayeli, Alexis (Frontiers in Neuroscience, 2021)
Introduction: The objective of our study was to evaluate musical perception and its relation to the quality of life in patients with bimodal binaural auditory stimulation. Materials and Methods: Nineteen adult patients with a cochlear implant (CI) for minimum 6 months, and moderate to severe contralateral hearing loss with a hearing aid (HA), and 21 normal hearing adults were included in this prospective, cross-sectional study. Pure-tone and speech audiometry, musical test evaluating sound perception characteristics and musical listening abilities, Munich questionnaire for musical habits, and the APHAB questionnaire were recoded. Performance in musical perception test with HA, CI, and HA+CI, and potential correlations between music test, audiometry and questionnaires were investigated. Results: Bimodal stimulation improved musical perception in several categories (sound brightness, roughness and clarity) in comparison to unimodal hearing, but CI did not add to HA performances in texture, polyphony or musical emotion and even appeared to interfere negatively in pitch perception with HA. Musical perception performances (sound clarity, instrument recognition) appeared to be correlated to hearing-related quality of life (APHAB RV and EC subdomains respectively) but not with speech performances suggesting that the exploration of musical perception complements speech understanding evaluation to better describe every-day life hearing handicap Conclusions: Testing musical sound perception provides important information on hearing performances as a complement to speech audiometry and appears to be related to hearing-related quality of life.